Molecular investigations of protriptyline as a multi-target directed ligand in alzheimer's disease - Bansode, Sneha B.; Jana, Asis K.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Joshi, Rakesh S.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (Plos One, 2014)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving multiple cellular and molecular processes. The discovery of drug molecules capable of targeting multiple factors involved in AD pathogenesis would greatly facilitate in improving therapeutic strategies. The repositioning of existing non-toxic drugs could dramatically reduce the time and costs involved in developmental and clinical trial stages. In this study, preliminary screening of 140 FDA approved nervous system drugs by docking suggested the viability of the tricyclic group of antidepressants against three major AD targets, viz. Acetylcholinesterase (AChE), beta-secretase (BACE-1), and amyloid beta (A beta) aggregation, with one member, protriptyline, showing highest inhibitory activity. Detailed biophysical assays, together with isothermal calorimetry, fluorescence quenching experiments, kinetic studies and atomic force microscopy established the strong inhibitory activity of protriptyline against all three major targets. The molecular basis of inhibition was supported with comprehensive molecular dynamics simulations. Further, the drug inhibited glycation induced amyloid aggregation, another important causal factor in AD progression. This study has led to the discovery of protriptyline as a potent multi target directed ligand and established its viability as a promising candidate for AD treatment.

Molecules with O-acetyl group protect protein glycation by acetylating lysine residues - Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Kashinath, K.; Kesavan, Suresh K.; Bhat, Shweta; Korwar, Arvind M.; Chougale, Ashok D.; Boppana, Ramanamurthy; Reddy, D. Srinivasa; Kulkarni, Mahesh J. (RSC Advances, 2016)
Pharmaceutical intervention for reduction of advanced glycation end products (AGEs) is considered as a therapeutic strategy to attenuate the pathogenesis of diabetes. Many molecules have been reported to possess antiglycation activity, one such example is acetylsalicylic acid (aspirin). It protects proteins from glycation by acetylating the lysine residues. Therefore, in this study we have synthesized and screened molecules containing free N-acetyl, O-acetyl and acetophenone groups. All the selected molecules in this study showed glycation inhibition but interestingly, only molecules with O-acetyl but not N-acetyl and acetophenone groups were capable of acetylating lysine residue. Furthermore, we have demonstrated that pre-acetylation or aspirin treatment prior to the induction of diabetes helps in reducing HbA1c and AGE formation in the streptozotocin induced diabetic mice. Hence pre-acetylation may have an additional therapeutic efficacy of reducing AGE levels in vivo. Incorporation of O-acetyl group into anti-diabetic molecules could be a useful strategy, as it may have an additive effect in reducing AGEs. Identification of such novel acetylating agents represents a new area in the drug discovery process.

Mass spectrometry based identification of galectin-3 interacting proteins potentially involved in lung melanoma metastasis - Dange, Manohar C.; Bhonsle, Hemangi S.; Godbole, Rashmi K.; More, Shyam K.; Bane, Sanjay M.; Kulkarni, Mahesh J.; Kalraiya, Rajiv D. (Molecular Biosystems, 2017)
Adhesive interactions between molecules on tumor cells and those on target organs play a key role in organ specific metastasis. Poly-N-acetyl-lactosamine (polyLacNAc) substituted N-oligosaccharides on melanoma cell surface glycoproteins promote lung specific metastasis via galectin-3 by facilitating their arrest and extravasation. This study reports the identification and characterization of galectin-3 interacting proteins using a combination of galectin-3 sepharose affinity and leucoagglutinating phytohemagglutinin (L-PHA) columns. A total of 83 proteins were identified as galectin-3 interacting glycoproteins, of which 35 were constituents of the L-PHA bound fraction, suggesting that these proteins carry polyLacNAc substituted beta 1,6 branched N-glycans. The identities of some of these proteins, like LAMP-1, LAMP-3, basigin, embigin, and alpha 5 and beta 1 Integrin, have been confirmed by western blotting, and functional relevance with respect to metastatic properties has been established.

Methylglyoxal attenuates insulin signaling and downregulates the enzymes involved in cholesterol biosynthesis - Deshmukh, Arati B.; Bai, Shakuntala; Aarthy, T.; Kazi, Rubina S.; Banarjee, Reema; Rathore, Rajeshwari; Vijayakumar, M. V.; H. V. Thulasiram; Bhat, Manoj Kumar; Kulkarni, Mahesh J. (Molecular Biosystems, 2017)
Methylglyoxal (MG) is a highly reactive dicarbonyl known to be elevated under the hyperglycemic conditions of diabetes and is implicated in the development of diabetic complications. Therefore, the current study investigates the role of MG in exacerbating insulin resistance at the insulin signaling level, as well as its effect on the global proteomic level. By using insulin sensitive rat muscle cells (L6) and Chinese hamster ovary (CHO) cells stably expressing the insulin receptor (IR) and a glucose transporter fused with green fluorescent protein (GLUT4-GFP), we have observed that MG impairs insulin signaling, inhibits GLUT4 translocation and reduces glucose uptake. SWATH MS analysis, a label-free quantitative mass spectrometric approach, showed altered expression of 99 proteins out of 2404 identified in response to MG treatment. These proteins are mainly involved in stress response, protein folding and proteolysis. Some of the deregulated proteins such as thioredoxin 2, glutathione S transferase, T complex protein 1 subunit beta (tcbp1), heat shock protein 90 and E3 ubiquitin ligase were previously reported to be associated with either diabetes or insulin resistance. Interestingly, aminoguanidine (AMG), a potent dicarbonyl scavenger, restored the deleterious effects of MG. For the first time, we report that MG induces downregulation of enzymes involved in cholesterol biosynthesis such as acetyl-CoA acetyltransferase, hydroxymethylglutaryl-CoA synthase, farnesyl pyrophosphate synthetase, squalene monooxygenase, and lanosterol synthase. GC MS analysis for sterol metabolites corroborated the proteomic results; MG significantly reduced cholesterol production whereas AMG treatment restored cholesterol production to levels similar to the control. Thus, MG leads to primary defects in insulin signaling and cellular abnormalities at the proteomic and metabolic levels, both of which may contribute to the development of insulin resistance.

Molecular investigation of glycated insulin-induced insulin resistance via insulin signaling and AGE-RAGE axis - Walke, Prachi B.; Bansode, Sneha B.; More, Nikita P.; Chaurasiya, Arvindkumar H.; Joshi, Rakesh S.; Kulkarni, Mahesh J. (Biochimica ET Biophysica Acta-Molecular Basis of Disease, 2021)
Hyperglycemic condition in diabetes promotes glycation of various plasma proteins including insulin. Glycation of insulin has been reported to reduce its biological activity. Reduced biological activity of glycated insulin could be either due to reduced affinity for the insulin receptor and impaired insulin signaling, or it can act as a ligand for the receptor for advanced glycation end products (RAGE) and activates oxidative stress and pro-inflammatory pathways leading to insulin resistance. This study investigates the effect of glycated insulin on both insulin and RAGE signaling. Glycated insulin treatment to Chinese hamster ovary (CHO-IR-GLUT4) cells stably expressing insulin receptor (IR) and glucose transporter fused with a green fluorescent protein (GLUT4-GFP) resulted in the impairment of insulin signaling, as the phosphorylation of IR and AKT significantly reduced, which affected GLUT4 translocation and glucose uptake. Moreover, it also activated RAGE signaling as observed by increased expression of NADPH oxidase accompanied by an increase in reactive oxygen species (ROS). Immunofluorescence study indicated the translocation of NF-kappa B to the nucleus upon treatment of glycated insulin. This was associated with increased RAGE expression, Caspase 3, and cell death. Downregulation of RAGE with the losartan treatment restored the impaired insulin signaling and glucose uptake. Additionally, in silico study demonstrated that glycated insulin has reduced binding affinity to insulin receptor and increased binding affinity to RAGE. Overall, this study demonstrates the role of glycated insulin in exacerbating insulin resistance by impairing insulin signaling as well as stimulating AGE-RAGE signaling.
Keywords: AGE; Diabetes; Glycation; Hyperglycemia; insulin; RAGE

Multiple-parallel-protease digestion coupled with high-resolution mass spectrometry: an approach towards comprehensive peptide mapping of therapeutic mAbs - Pradhan, Gauri; Sneha, J. M.; Sonwane, Babasaheb P.; Santhakumari, B.; Rao, Alka; Kulkarni, Mahesh J. (Journal of Proteomics, 2021)
Therapeutic monoclonal antibodies (mAbs) are structurally large and complex molecules. To be safe and efficacious, a biosimilar mAb must show high similarity to its reference product in Critical Quality Attributes (CQA). mAbs are highly sensitive to protein expression, production, manufacturing, supply chain, and storage conditions. All these factors make biosimilar mAbs intrinsically susceptible for variability during production. Accordingly, several lots of references and tests are required to establish the biosimilarity of a test mAb. The primary structure is a CQA of a mAb affecting its safety and efficacy. Here, we apply peptide mapping as an analytical method to decipher the primary structure and associated modifications for a quick quality assessment of TrastuzumAb and RituximAb innovator and biosimilar. A multiple-parallel-protease digestion strategy followed by high-resolution mass spectrometric analysis consistently achieved 100% sequence coverage along with reliable detection of post-translational modifications. Additionally, the use of supporting methods such as intact mass analysis and circular dichroism helped us to decipher the primary and higher order structures of these mAbs. We identify discernible variations in the profile of the innovator and biosimilar mAbs and validate the method for quick yet deep comparability analysis of the primary structure of biosimilar mAbs sold in the market. Significance: Peptide mapping using bottom-up approach is one of the most common methods for the characterization of therapeutic monoclonal antibodies. Herein, we describe a multi-parallel-protease digestion strategy using a combination of five different proteases followed by high-resolution mass spectrometric analysis with TrastuzumAb and RituximAb as an example. This resulted in a comprehensive identification of peptides with increased reliability and identification of different PTMs. Additional supporting orthogonal methods like intact mass and higher-order structure analysis helped evaluate broader conformational properties.
Keywords: LC-MS/MS; PTM; RituximAb; Therapeutic monoclonal antibodies; TrastuzumAb

Mechanistic insights on anserine hydrolyzing activities of human carnosinases - Pandya, Vaibhav Kumar; Shankar, S. Shiva; Rajesh, S.; Rathore, Rajeshwari; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (Biochemica ET Biophysica Acta- General Subjects, 2023)
Anserine and carnosine represent histidine-containing dipeptides that exert a pluripotent protective effect on human physiology. Anserine is known to protect against oxidative stress in diabetes and cardiovascular diseases. Human carnosinases (CN1 and CN2) are dipeptidases involved in the homeostasis of carnosine. In poikilothermic vertebrates, the anserinase enzyme is responsible for hydrolyzing anserine. However, there is no specific anserine hydrolyzing enzyme present in humans. In this study, we have systematically investigated the anserine hydrolyzing activity of human CN1 and CN2. A targeted multiple reaction monitoring (MRM) based approach was employed for studying the enzyme kinetics of CN1 and CN2 using carnosine and anserine as substrates. Surprisingly, both CN1 and CN2 can hydrolyze anserine effectively. The observed catalytic turnover rate (Vmax/[E]t) was 21.6 s-1 and 2.8 s-1 for CN1 and CN2, respectively. CN1 is almost eight-fold more efficient in hydrolyzing anserine compared to CN2, which is comparable to the efficiency of the carnosine hydrolyzing activity of CN2. The Michaelis constant (Km) value for CN1 (1.96 mM) is almost three-fold lower compared to CN2 (6.33 mM), representing higher substrate affinity for anserine-CN1 interactions. Molecular docking studies showed that anserine binds at the catalytic site of the carnosinases with an affinity similar to carnosine. Overall, the present study elucidated the inherent promiscuity of human carnosinases in hydrolyzing anserine using a sensitive LCMS/MS approach.
Keywords: Anserine; Carnosinase; Carnosine; Diabetes; LC-MS; MS; Multiple reaction monitoring (MRM); Promiscuity

Multi-dimensional impact of captopril modification on human serum albumin - Ghosh, Amrita; Jani, Vinod; Sonavane, Uddhavesh; Naphade, Anvi N.; Joshi, Rajendra; Kulkarni, Mahesh J.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2024)
Captopril is a thiol drug, widely used for the management of hypertension and cardiovascular diseases. Reactive thiols are found to covalently modify the cysteines of plasma proteins and affect their structure and function. Human serum albumin (HSA) is prone to undergo modification by various low molecular weight compounds, including drugs. Cysteine34 (Cys34) in HSA has a free thiol group with antioxidant properties, considered to be the most redox-sensitive amino acid in plasma. Through mass-spectrometric analysis, we demonstrate for the first time that captopril forms a disulfide adduct at Cys34 residue and increases the protease susceptibility of HSA to trypsin. As evidenced by our biophysical and electron microscopy studies, HSA undergoes structural alteration, aggregation and morphological changes when treated with different captopril concentrations. Molecular dynamics studies further revealed the regions of secondary structural changes in HSA due to disulfide adduct formation by captopril at Cys34. It also elucidated the residues involved in the noncovalent interactions with captopril. It is envisaged that structural change in HSA may influence the efficacy of drug delivery as well as its own biological function. These findings may thus provide significant insights into the field of pharmacology intriguing further investigation into the effects of long-term captopril treatment.
Keywords: Captopril; Electron microscopy; Human serum albumin; Mass spectrometry; Molecular dynamic simulation; Spectrophotometry